Gọi \(F(x)\) là một nguyên hàm của hàm số \(f(x)=x^2(x-2)\) sao cho \(F(1)=\dfrac{7}{12}\). Khi đó \(F(x)\) là
\(F(x)=\dfrac{x^4}{4}+\dfrac{x^3}{3}\) | |
\(F(x)=\dfrac{x^4}{4}-\dfrac{x^3}{3}+\dfrac{2}{3}\) | |
\(F(x)=\dfrac{x^4}{4}-\dfrac{2x^3}{3}+1\) | |
\(F(x)=\dfrac{x^4}{4}+\dfrac{2x^3}{3}-\dfrac{1}{3}\) |
Chọn phương án C.
\(\begin{aligned}F(x)&=\displaystyle\int f(x)\mathrm{\,d}x=\displaystyle\int\left(x^3-2x^2\right)\mathrm{\,d}x\\
&=\dfrac{x^4}{4}-\dfrac{2x^3}{3}+C.\end{aligned}\)
\(\begin{aligned}\text{Mà }F(1)=\dfrac{7}{12}\Leftrightarrow&\,\dfrac{1^4}{4}-\dfrac{2\cdot1^3}{3}+C=\dfrac{7}{12}\\
\Leftrightarrow&\,C=1.\end{aligned}\)
Vậy \(F(x)=\dfrac{x^4}{4}-\dfrac{2x^3}{3}+1\).